MODEL PENGEMBANGAN PEMBINAAN KEPRIBADIAN AGAMA SANTRI DI PONDOK PESANTREN TAHFIZUL QURAN MUALLIMIN MUHAMMADIYAH SAWAH DANGKA - Efendi, Indra; Sesmiarni, Zulfani (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of writing this article is to provide an overview of the model for the development of religious personality development based on in-depth observation of what is practiced by the Islamic boarding school community in order to develop the personality of the students, such as at the Tafizul Quran Muallimin Muhammadiyah Islamic boarding school, Sawah Dangka. This research was conducted with a qualitative approach in the form of ethnography. The results of this study indicate that in developing the religious personality development of students through the formal learning and teaching process it is organized classically based on the curriculum of the Ministry of Religion and Islamic Boarding Schools, character and personality development, as well as extra-curricular activities with the pondok system. The Madrasah curriculum consists of a combination of the Ministry of Religion curriculum and Muhammadiyah curriculum and Islamic Boarding Schools. Specific lessons are tahfizul Quran, Arabic and the Yellow Book with mandatory activities such as tahfizul quran with targets at each grade level, hizbul wathan and others and supported by other extracurricular activities whose output produces alumni who are widely accepted at universities in the middle East.